Unveiling the inner morphology and gas kinematics of NGC 5135 with ALMA. Issue 4 (3rd March 2018) - Sabatini, G; Gruppioni, C; Massardi, M; Giannetti, A; Burkutean, S; Cimatti, A; Pozzi, F; Talia, M
Abstract: The local Seyfert 2 galaxy NGC 5135, thanks to its almost face-on appearance, a bulge overdensity of stars, the presence of a large-scale bar, an active galactic nucleus (AGN) and a supernova remnant, is an excellent target to investigate the dynamics of inflows, outflows, star formation, and AGN feedback. Here, we present a reconstruction of the gas morphology and kinematics in the inner regions of this galaxy, based on the analysis of Atacama Large Millimeter Array (ALMA) archival data. For this purpose, we combine the available ∼100 pc resolution ALMA 1.3 and 0.45 mm observations of dust continuum emission, the spectroscopic maps of two transitions of the CO molecule (tracer of molecular gas mass in star-forming and nuclear regions), and of the CS molecule (tracer of the dense star-forming regions) with the outcome of the spectral energy distribution decomposition. By applying the 3D barolo software (3D-Based Analysis of Rotating Objects from Line Observations), we have been able to fit the galaxy rotation curve using a 3D tilted-ring model of the disc. Most of the observed emitting features are described by our kinematic model. We also attempt an interpretation for the emission in a few regions that the axisymmetric model fails to reproduce. The most relevant of these is a region at the northern edge of the inner bar, where multiple velocity components overlap, as a possible consequence of the expansion of a superbubble.